Issues around violence in schools - Collins, Lauren W.; Landrum, Timothy J.; Cook, Bryan G. (Advances in learning and behavioral disabilities ;, 2023)
It is challenging to understand the complexity and multiple causes of school violence. Given the apparent rise in many forms of violence in schools, and the dire consequences to those impacted by violence, it is vital to better support children and youth in both preventing violence and responding appropriately. Issues Around Violence in Schools explores a number of topics related to violence that occurs in schools or with school-aged children and youth. Authors address the nature and extent of violence in schools - including mass shootings but also other forms of violence - and the relationships and intersections among mental health, special education, and school violence in general. They consider positive approaches to mental health, behavior, and overall climate in schools, analysing both disciplinary practices and interventions and supports and their relationship to school violence. Key insights are presented regarding bullying, positive approaches to behavioral and social/emotional concerns, and the promise of threat assessment for mitigating violence and connecting students to needed supports. This volume provides an overview of key areas of promise for improved research and practice, such that schools are better positioned to mitigate violence, and to respond in positive, supportive ways to those who may be impacted by violence.